Pharmacokinetic, Safety, and Tolerability Evaluations of Gepotidacin (GSK2140944) in Healthy Japanese Participants. Issue 1 (5th December 2022) - Barth, Aline; Hossain, Mohammad; Perry, Caroline R.; Gross, Annette S.; Ogura, Hirofumi; Shabbir, Shaila; Thomas, Sebin; Dumont, Etienne F.; Brimhall, Darin B.; Srinivasan, Meenakshi; Swift, Brandon
Abstract: Gepotidacin is a novel, bactericidal, first‐in‐class triazaacenaphthylene antibiotic in late‐phase development for uncomplicated urinary tract infection and uncomplicated urogenital gonorrhea. Two clinical studies were conducted to assess the pharmacokinetics (PK) and interethnic comparisons of oral gepotidacin (free‐base and to‐be‐marketed mesylate formulations) administered as single doses ranging from 1500 to 3000 mg in fed and fasted states, and as 2 × 3000‐mg doses given 12 hours apart under fed conditions in healthy participants of Japanese ancestry. Dose proportionality was observed in plasma exposures, and comparable area under the concentration‐time curve (AUC) and maximum concentration were observed in fed and fasted states. Interethnic comparisons for Japanese versus non‐Japanese participant data showed slightly higher plasma maximum concentration (7%‐30%) yet similar plasma AUCs; slightly lower urine AUCs (11%‐18%) were observed. The slightly higher plasma exposures in healthy Japanese versus White participants in the same study were attributed to lower mean body weights (64 kg versus ≈80 kg). Adverse events were primarily gastrointestinal, and when administered with food, gastrointestinal tolerability was improved. Overall, the gepotidacin PK and safety‐risk profiles in healthy Japanese support potential evaluation of the global clinical doses in future studies.